Development of Bullous Disease during Treatment of Pulmonary Marginal Zone B-Cell Lymphoma - S. Ansari; H. Dubaybo; E. Levi; B. A. Dubaybo (Case Reports in Pulmonology)
We describe an unusual case of severe pulmonary bullous disease developing during treatment of marginal zone B-Cell lymphoma (MALT) involving the pulmonary parenchyma. The patient originally presented with pneumonia-like symptoms along with hemoptysis and was diagnosed with MALT lymphoma after a video-assisted thoracic surgical (VATS) lung biopsy. Computed tomography (CT) of the chest at diagnosis revealed multiple opacities, but no bullous disease. During the ensuing 4 years, and while on chemotherapy for the MALT lymphoma, sequential CT and pulmonary function tests revealed the development of progressive bullous disease resulting in the replacement of large portions of the lung parenchyma with bilateral bullae. This complication is rare, has been reported only once before in a patient with concomitant amyloidosis, and may be related to activation of proteolytic enzymes by lymphoma cells or chemotherapeutic agents.